Japanese real‐world study of sequential nivolumab and ipilimumab treament in melanoma. Issue 11 (17th September 2019) - Tsutsumida, Arata; Fukushima, Satoshi; Yokota, Kenji; Yoshikawa, Shusuke; Yamasaki, Osamu; Tanemura, Atsushi; Okuyama, Ryuhei; Uhara, Hisashi; Muto, Yusuke; Miyashita, Azusa; Akiyama, Masashi; Kaji, Tatsuya; et al.
Abstract: To describe the treatment patterns of nivolumab and ipilimumab in Japan, a retrospective observational study was conducted in melanoma patients who received nivolumab and ipilimumab sequentially. Patients who received nivolumab and ipilimumab in combination were excluded from this study. Efficacy was evaluated by the Response Evaluation Criteria in Solid Tumors (RECIST) in terms of the overall response rate (ORR), progression‐free survival (PFS), and disease control rate (DCR). Overall survival (OS) was also evaluated. Safety was assessed by the Common Terminology Criteria for Adverse Events (CTCAE). The treatment for all 68 patients enrolled involved switching from nivolumab to ipilimumab in 61 patients and switching from ipilimumab to nivolumab in seven patients. Switching occurred because of progressive disease in 55 patients and adverse events in eight patients. The median number of ipilimumab doses was three. Ipilimumab treatment achieved an ORR and DCR of 4.9% and 21.3%, respectively, and the median OS from start of ipilimumab was 7.0 months. During the study period, no new safety signals were noted. Independent factors which were indicative of poor prognosis for PFS were high neutrophil‐to‐lymphocyte ratio (NLR) and high C‐reactive protein (CRP) levels before ipilimumab treatment. An evaluation over a washout period indicated that no significant relationship existed with efficacy or safety. For the sequential administration of nivolumab and ipilimumab in Japanese melanoma patients, switch from nivolumab to ipilimumab was common, and the major reason for switching was progressive disease. The major prognostic factors for ipilimumab PFS after nivolumab were NLR and CRP before ipilimumab treatment.